Harry Potter and the philosopher's stone - Rowling, J. K. (London : Bloomsbury, 2004)
Presents an ancient Greek version of J.K. Rowling's classic novel about eleven-year-old Harry Potter who discovers that he is a wizard and suddenly finds himself at Hogwarts School of Witchcraft and Wizardry.
5-8.
5-8
Keywords: Fantasy; Greek language materials; Hogwarts School of Witchcraft and Wizardry (Imaginary organization) -- Fiction; Potter, Harry (Fictitious character) -- Fiction; Schools -- Fiction; Witches -- Fiction; Wizards -- Fiction; Greek language; Hogwarts School of Witchcraft and Wizardry (Imaginary organization) -- Fiction; Potter, Harry (Fictional character) -- Fiction; School stories; Witches -- Fiction; Wizards -- Fiction; England -- Fiction; England -- Fiction; Fantastic fiction